Os professores diante de um novo trabalho com a leitura: modos de fazer semelhantes ou diferentes? - Buzzo, Marina Gonçalves (2008)
This research has as a wider objective to investigate the representations about the educational work built in an oral text produced jointly by two teachers of Portuguese Language after the accomplishment of a specific work activity. More specifically, we investigate if it similar or different representations appear in the each one of their turns and the linguistic-discoursive characteristics that contribute to distinguish differences and likeness among their didactic procedures. Because of that, we assume the theoretical-methodological presuppositions of the sociodiscoursive interactionism as larger reference source (Bronckart, 1997/99; 2004c; 2006), associated to the theoretical contributions of the Activity Ergonomy (Amigues, 2003, 2004a; Saujat, 2002, 2004a) and to the theoretical-methodological contributions from the Activity-Clinic (Faïta, 2004; Clot, 1999; 2004a), for a deeper study questions linked to the educational work. We will use for the complementation of the data analysis model suggested by Bronckart (1997/99; 2004c; 2006) and reformulated by Machado (Machado, 2008/in press) some procedures of Kerbrat- Orecchioni (1990; 1996) and Charaudeau (1992). The data were collected in a crossed self-confrontation, whose verbalizations had as a central topic the teaching of the written production of the reading diary, didactic procedure for us offered and applied by two Portuguese teachers in their reading classes. For the self-confrontation accomplishment, we filmed, with each one of them, the first introductory class and, after one semester, a diaries discussion class produced by the students. In the analyses, we tried to observe the organizational, enunciative and semantic characteristics, in search of indexes that revealed us how the teachers confronted themselves with likeness and contrasts from the observation of the accomplished activities. These analyses tried to reveal which acting interpretative figures the teachers built in the self-confrontation texts with bigger frequency in relation to the constituent elements of the educational work and of the human acting in general. The results show how each teacher sees the activity of each other and how each one reacts to this direct confrontation, in other words, the contrasts prove the peculiar style of each one in their performance in the classroom and, with that, work collective traces, for, when they look for a back-up in the representations built by the work collective, they use different discursive strategies to defend themselves of the criticisms occurred between themselves, when they are comparing each other. With relation to the likeness detected, they ones point to the educational gender common traces in the specific teaching activity emphasized or the real point of this activity